M. BURKHALTER, S. CHRISTIAN (eds.) - Konrad Wachsmann and the Grapevine Structure - Jerez Abajo, Enrique (ZARCH, 2018)
Marianne Burkhalter, Christian Sumi (eds.) Konrad Wachsmann and the Grapevine Structure Park Books, Zürich, 2018, 152 páginas. Idioma: inglés. 48€. ISBN: 978-3-03860-110-4